A Scoping Review of Maternal Birth Experience in Low- and Middle-Income Countries from 2014-2024 - Madhurima Pal; Qu, Sarah; Alizadeh, Anita; Lu, Andy; Ali Sindhu, Hussain; Nwankwo, Chizitere (Journal of Maternal and Child Health, 2026)
Background: Childbirth experiences differ widely, shaped by cultural beliefs, socioeconomic status, healthcare infrastructure, and delivery location. In low- and middle-income countries (LMICs), limited access to quality care and higher maternal mortality rates deeply affect women’s experiences and outcomes. While prior studies have typically examined economic, social, or structural influences independently, a comprehensive approach that integrates these domains is needed. This study aims to examine the economic, social, and structural factors influencing maternal experiences in LMICs and assess how these factors shape both the choice of delivery location and maternal care experience.Subjects and Method: A literature search of studies from 2014 to 2024 was conducted using MEDLINE and Google Scholar. Controlled vocabulary (e.g., MeSH terms) and Boolean operators combined terms such as “midwives,” “birth assistants,” “LMICs,” “hospital birth,” and “maternal mortality rates.” Only peer-reviewed quantitative and qualitative English-language studies examining maternal birth experience in  LMICs were included. Grey literature, reviews, and opinion pieces were excluded. Findings were organized using a global framework on maternal health determinants.Results: Of 114 articles identified, 8 met the inclusion criteria, covering studies from Bangladesh, Ethiopia, rural Sierra Leone, Kenya, rural Zambia, Chiapas (Mexico), and Eritrea. These studies revealed that maternal experience and delivery location are shaped by economic, social and structural factors. Hospital fees and informal costs discouraged facility-based births, while limited education, cultural norms and male-dominated decision-making reduced women’s autonomy in choosing their delivery location. Structural challenges, including staff shortages, lack of privacy, and poor rural access, further limited hospital deliveries.Conclusion: Maternal birth experiences in LMICs are influenced by hospital delivery costs, cultural beliefs, limited education and awareness, and inadequate healthcare facilities, which reduce access to quality care and undermine women’s autonomy. Targeted interventions, such as affordable, culturally sensitive, and accessible healthcare and education-focused initiatives, are essential to enhancing maternal birth experiences and outcomes.